Kegiatan “Design For Kids” Bagi Generasi Alpha Di Coding Lab - rezky, syarifah; Siregar, Siti Julianti; Wahyuni, Meri Sri; Gaol, Nur Yanti Lumban; Natasha, Syarifah Fadillah (Jurnal Masyarakat Indonesia (Jumas), 2023)
Graphic design has an important role in developing children's creativity. In utilizing graphic design for children of the alpha generation, it is important to choose images and design elements that are age-appropriate and appealing to them. Design should take children's visual intelligence into account, with the use of bright colors, clear contrasts and easily recognizable images. The main role of graphic design in encouraging children's creativity is visual stimulation, exploration with design tools, visual creativity in the form of imagination and ideas in the child's right brain. The Coding Lab facilitates children of the alpha generation, where the children of the alpha generation are born in 2011 until now. To develop their dominant talents and creativity, they are already familiar with gadgets by utilizing the role of multimedia technology with interactive visual learning models, discussions and independent basic assignment projects. The purpose of this activity is to have a positive impact on children, especially the role of technology to explore children's imagination and creativity.